SME INNOVATION AND SOCIAL MEDIA ON INTENTION TO VISIT TERNATE CITY WITH DESTINATION IMAGE AS THE MODERATING VARIABLE - Aldina Shiratina; Yanto Ramli; Haniruzila Md Hanifah (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2022)
The development of the Indonesian tourism sector has been improving with the introduction of Wonderful Indonesia around the world. In accordance with the development of the tourism section, building the Small Medium Enterprises (SME) innovatively is very important. The improvement of the tourism sector has given the people around the tourism area new hopes and better income from the tourists' spending. The city of Ternate, with 22 tourism objects, has been one of the potential tourist sites and has been one of the favorite tourist sites of Indonesia. However, the number of tourists visiting the city of Ternate has been declining. The study intends to find out how to enhance the local SME segments and develop them innovatively based on the variable of innovation, social media, and destination image as the mediating variable towards the dependent variable of intention to visit. The sample size of this study is based on 175 tourists visiting the tourist objects in the city of Ternate. The results indicate that SME innovation and social media significantly influence the intention to visit.